BUILDING THE FORECASTING SYSTEM OF DECISION-MAKING IN CLOUD COMPUTING - Nguyễn Tấn Thuận; Trương Tiến Vũ (Tạp chí Khoa học Đại học Đà Lạt)
This paper describes the forecasting system of decision-making on cloud computing by applying the algorithm C4.5. This paper focus on the visualized software solution with the purpose of providing multiple services in the fields of business, commerce, education, health, tourism, etc. by collecting data via internet and building decision tree to predict forecast report to user through the algorithm C4.5. This paper mainly highlights different methods and decisions within the system by many criteria, subdivisions, processes, and other features of C4.5. The paper describes the C4.5 as the optimized algorithm through the division standard of classification in which the Information Gain is used as the criteria for evaluating algorithm C4.5.